Continuous Diastereomeric Kinetic Resolution—Silybins A and B - David Biedermann; Martina Hurtová; Oldřich Benada; Kateřina Valentová; Lada Biedermannová; Vladimír Křen (Catalysts, 2021)
The natural diastereomeric mixture of silybins A and B is often used (and considered) as a single flavonolignan isolated from the fruit extract of milk thistle (Silybum marianum), silymarin. However, optically pure silybin diastereomers are required for the evaluation of their biological activity. The separation of silybin diastereomers by standard chromatographic methods is not trivial. Preparative chemoenzymatic resolution of silybin diastereomers has been published, but its optimization and scale-up are needed. Here we present a continuous flow reactor for the chemoenzymatic kinetic resolution of silybin diastereomers catalyzed by Candida antarctica lipase B (CALB) immobilized on acrylic resin beads (Novozym® 435). Temperature, flow rate, and starting material concentration were varied to determine optimal reaction conditions. The variables observed were conversion and diastereomeric ratio. Optimal conditions were chosen to allow kilogram-scale reactions and were determined to be −5 °C, 8 g/L silybin, and a flow rate of 16 mL/min. No significant carrier degradation was observed after approximately 30 cycles (30 days). Under optimal conditions and using a 1000 × 15 mm column, 20 g of silybin per day can be easily processed, yielding 6.7 and 5.6 g of silybin A and silybin B, respectively. Further scale-up depends only on the size of the reactor.